Larvicidal and nematicidal activities of 3-acylbarbituric acid analogues against Asian Tiger Mosquito, Aedes albopictus, and Pine Wood Nematode, Bursaphelenchus xylophilus. - Seo, S; Lee, H; Lee, J; Jeong, Y; Kwon, H; Moon, J; Moloney, M; Park, I (MDPI, 2017)
Widespread concern for the occurrence of resistant strains, along with the avoidance of the use of highly toxic insecticides and their wide environmental dispersal, highlights the need for the development of new and safer pest control agents. Natural products provide inspiration for new chemical entities with biological activities, and their analogues are good lead compounds for the development of new pest control agents. For this purpose, we evaluated the larvicidal and nematicidal activities of 48 3-acylbarbituric acid analogues against the Asian tiger mosquito, Aedes albopictus and the pine wood nematode, Bursaphelenchus xylophilus, organisms of increasing global concern. Among the 48 3-acylbarbituric acid analogues, four compounds-10, 14d, 14g and 19b-showed >90% larvicidal activity against Ae. albopictus at 10 μg/mL concentration, and one (compound 10) showed the strongest larvicidal activity against Ae. albopictus, with a LC50 value of 0.22 μg/mL. Only compound 18 showed strong nematicidal activity against pine wood nematode. Most active compounds possessed similar physicochemical properties; thus, actives typically had ClogP values of around 1.40-1.50 and rel-PSA values of 16-17% and these similar cheminformatic characteristics reflect their similar structure. This study indicates that active 3-acylbarbituric acids analogues have potential as lead compounds for developing novel mosquito control agents.